Criteria for a suitable reference cuff for validation studies of blood pressure measuring devices in people with arm circumference between 43 and 50 cm - Palatini, Paolo; Fania, Claudio; Benetti, Elisabetta; Saladini, Francesca; Battista, Francesca; Ermolao, Andrea (Blood pressure monitoring, 2023)
Recommendations about the dimensions of the reference cuff for device validations in people with arm size >42 cm are still unavailable. The aim of this study was to identify the criteria for an appropriate reference cuff for validation studies in people with upper arm circumference between 43 and 50 cm. In 20 adults with upper arm circumference between 43 and 50 cm (X-large group), 34 subjects with arm circumference between 37 and 42 cm and 78 subjects with arm circumference <37 cm cylindrical and tronco-conical cuffs were compared. In all participants, the pressure transmitted to the arm under the two cuffs was measured using a paper-thin pressure sensor. In the X-large group, all participants had an arm slant angle <86.0°. In this group, the difference between the pressure detected on the arm surface with the sensor using the cylindrical versus the tronco-conical cuff (13.5 mmHg) was larger than in the group with an arm circumference of 37-to 42 cm and the group with a circumference <37 cm (3.7 and 0.6 mmHg, respectively, P  < 0.001 versus both). In the whole sample, the between-cuff pressure difference was proportional to the conical shape of the arm ( P  < 0.001). These data suggest that in people with arm size between 43 and 50 cm the reference cuff for validation studies should have a conical shape with an 84-85° slant angle. To comply with current guidelines, an 18.5 × 37.0 cm bladder should be used which would allow proper cuffing in the large majority of subjects.